Maintaining the Performance and Sustainability of MSMEs with E-Commerce: Research during the Covid-19 Pandemic - Dekeng Setyo Budiarto; Ervana Vivianti; Rani Eka Diansari (Universitas Hayam Wuruk Perbanas, 2020)
Even though they have a considerable contribution to economic growth, MSMEs have various business sustainability problems. This study aims to test whether e-commerce, information technology, business network affects performance. Besides, this study also examines the effect of performance on business sustainability. The data were obtained employing a questionnaire given to 193 MSMEs owners in Yogyakarta. This research was conducted during the COVID-19 pandemic so that questionnaires were distributed both online and offline. The analysis results using PLS show that e-commerce and business networks affect performance, while information technology does not affect performance. Furthermore, performance affects the sustainability of SME businesses. This research implies that there is still need for support from the government so that MSMEs can take advantage of e-commerce and expand business networks to survive during the Covid-19 pandemic